Dos saberes docentes à prática pedagógica na Escola Vila: contribuição para a formação de professores - Sotero, Morena Cristal Limaverde (2018)
The debate on education paradigm is relevant facing the imposed challenges by an ethical and ecological crisis which permeates society. A paradigm can be understood as a force acting over a society which submits to certain dogmas and ideologies. Such elements are absorbed and unconsciously reproduced by the people, operating on how they deal with themselves, with the others and with nature. (MORIN, 2010). The present research brings as an investigative field VILA School, in Fortaleza, since it was built on a teaching context over 36 years proposing an education paradigm starting from an Ecosystemic Pedagogical approach, with its curricular principle based on empathy, self-awareness, collaborative work, dialogue with local and global community and creativity. As a starting point we investigated if the teacher’s knowledge related to Vila school pedagogical praxis is contemplated on training activities offered to its teachers. To do so, a qualitative research was held through a focal group with employed teachers and semi structured interviews with coordinators. Data was then processed using IRAMUTEQ software, generating five types of discussion. The analyzed results were organized in two phases: the first with the identified teacher’s knowledge; and the second with the knowledge categories according to the eight dimensions applied on teachers training, proposals of Sousa and Placco (2016). Among the analyzed teacher’s knowledge, it stands out being open to “what’s new”, sensitiveness and planetary consciousness. About the teacher’s training, it is clear the relevance of multidimensionality on teacher’s knowledge, high lightening the dimension we add to those on which we are based upon – Contact with Nature – as a learning source of knowledge for a paradigmatic transformation. We conclude that such investigation may contribute to creating future learning proposals of VILA teachers and possibly other teaching proposals which consider ethic and ecology as guidelines to school learning